The relationship between smoking cessation history and significant liver fibrosis among the population with metabolic dysfunction-associated steatotic liver disease in the United States. - Zhongtao Li; Hao Guo; Hongyu He; Shu Wang; Shufen Pei; Liang Xie (PLoS ONE)
Background Smoking was identified as a risk factor for the development of liver fibrosis in patients with metabolic dysfunction-associated steatotic liver disease (MASLD). However, the association between smoking cessation history and the development of liver fibrosis remains unclear. This study was intended to analyze the association between smoking cessation history and significant liver fibrosis in adult MASLD participants in the United States. Methods This study utilized data from 2643 patients with MASLD from the National Health and Nutrition Examination Survey (NHANES). Significant liver fibrosis was detected based on transient elastography measurements. According to the smoking questionnaire data, patients were categorized as non-smokers, ex-smokers and current smokers. A multivariate logistic regression analysis, adjusted for weights, was performed to investigate the relationship between smoking cessation history and the presence of significant liver fibrosis in participants with MASLD. Results A total of 2643 patients with MASLD were included in this study. Compared with non-smokers, ex-smokers had a slightly elevated risk of developing significant liver fibrosis (OR: 1.07, 95% CI: 1.02-1.13). Specifically, a positive correlation was observed between patients who quit smoking for < 20 years and significant liver fibrosis (OR: 1.07, 95% CI: 1.01-1.15). Furthermore, MASLD patients who started regularly smoking at an age of ≤ 20 years (OR: 1.09, 95% CI: 1.02-1.16) and had a smoking duration of ≥ 10 years before quitting (OR: 1.10, 95% CI: 1.02-1.18) were also highly correlated with an increased likelihood of developing significant liver fibrosis. Conclusions This study revealed that individuals with MASLD who have ceased smoking exhibit an elevated risk for significant liver fibrosis when compared to those who never smoked. It is highly emphasized that MASLD patients who quit smoking for < 20 years, started regularly smoking at an age of ≤ 20 years, and had a smoking duration of ≥ 10 years before quitting should be extremely vigilant regarding the risk of significant liver fibrosis.